Antimicrobial Resistance Profiles in Vibrio spp. and Aeromonas spp. from Pangasius Fish: Detection and Identification from the Three Markets at Siem Reap Province, Cambodia (International Journal of Veterinary Medicine and Animal Science, 2024)
Pangasius fish carry various bacteria, notably Vibrio spp. and Aeromonas spp., which concern human health risks. They affect fish production and also produce harmful toxins for humans. The more antibiotics used in production, the greater the risk of antibiotic-resistant bacteria dominating competition at the antimicrobial resistance level. The study used 30 samples collected from three markets in Siem Reap, which were tightly packed in cooler bags during transport. The experiments were performed at the Microbiology Laboratory at RUA. These two bacteria can be detected using selective mediums known as TCBS Agar and MacConkey Agar. The purified colonies were then identified and characterized by gram stain, biochemical tests including catalase, oxidase, TSI, and motility test, and then confirmed strains using API 20E Version 5.0 system. The antibiotic susceptibility test was conducted using the disk diffusion method with 7 different drugs. The result showed that the total presence of Vibrio parahaemolyticus (n=12) was about 40% and Aeromonas hydrophila (n=14) was about 46.67%. Consequently, both bacteria had strong resistance to Ampicillin and Colistin Sulphate but were highly sensitive to Florfenicol, Sulfamethoxazole/Trimethoprim, and Oxytetracycline. In conclusion, the significant presence of these bacteria in pangasius fish poses health risks. The use of antibiotics often leads to bacterial immunity and antimicrobial resistance in which both bacteria show resistance to Ampicillin and Colistin Sulphate. This emphasizes the need for a cautious approach to antibiotic use to safeguard human health and maintain efficacy in pangasius fish.